A brief history of the negotiations on the International Treaty on Plant Genetic Resources for Food and Agriculture - Esquinas-Alcázar, José; Hilmi, Ángela; López Noriega, Isabel (2012)
Sixth chapter of the book Crop Genetic Resources as a Global Commons. Challenges in International Law and Governance. Edited by Michael Halewood, Isabel López Noriega and Selim Louafi. Published in 2012 by Routledge as part of the Earthscan book series "Issues in Agricultural Biodiversity".